STUDY THE POTASSIUM STATUS IN SOIL OF SOME AGRICULTURAL EXPANSION REGIONS WESTERN OF IRAQ - A. H.I.Al-Bayati (Mesopotamia Journal of Agriculture)
The present study was carried out to investigate the potassium status at soils of some agricultural expansion regions western of Iraq , and classify these soils according to its nutrition storage .To achieve the study aims , ten regions cultivated with wheat for a period not less than five years and similar in the soil management techniques had been selected. These are distributed in a way that ensures the inclusion of the majority of agricultural expansion regions of the governorate of Al-Anbar. Namely Al-Qiam, Haditha, Al-Baghdady, Hit, Thirthar, Al-Habanya, Km 98 Oasis, Fehadi Oasis, Horan Oasis, Kishety Oasis. The selected regions were morphological descripted and classified than soil samples were taken from every horizon to determination some physical,chemical and mineralogical properties.The results could be summarized as following :- Water soluble-K values of studied soils were ranged from 0.004 – 0.019 C mol.kg-1, while the exchangeable-K values were ranged from 0.193 – 0.559 C mol.kg-1 . It is noticed that there was a gradual decrease in the soil content of form with depth .With respect to the soil content of the non-exchangeable-K its values were ranged from 0.332-0.878 C mol.kg-1. In addition, these soils were characterized by high mineralogical-K content, which was compose 96.06% from the total-K, where as the total-K is ranged from 29.78 – 31.41 C mol.kg -1. 1- The soil fertility evaluation according to its content of available-K showed that most studied soil regions had high content of potassium that can be absorb by plant. More than half of the studied regions were classified as highly storage-K soils which were able to be released, while other regions were classified as low storage-K, according to the used world classification.